From a Business Point of View Study the Importance of Event Management Services of Specific Company - Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Laxmi Lydia, E.; Shankar, K. (Opción, 2019)
Organizing, planning and execution of live events are including in event management. In current days a number of event management services are available, it include a conference, a product or brand launch, a concert, an exhibition, a wedding planning and many more. It can consider that event management is the extended type of advertisement so it will become more attractive. With a survey it is projected that as separate industry it grows 30% per annum. This paper studies the different factors of event manage- ment and importance of with business point of view.